Association between Vitamin D3 deficiency and Oxidative stress in Non-Communicable Diseases - Ahmed Mohammad ZaKi; hussein, Jian Lateif; Nahla A.A. Abad Aljabar; Salih Omer Haji (Zanco Journal of Pure and Applied Sciences, 2022)
A non-communicable disease (NCD) is a disease that is not transmissible directly from one person to another. NCDs in this study include most heart diseases and diabetes. Vitamin D3 (Vit. D3) deficiency is one of the most common nutritional deficiencies worldwide, and it raises the risk of the non-communicable diseases (NCDs), also the relation to increasing oxidative stress in NCDs patients. The present study is focusing on the relationship between Vit. D3 deficiency and oxidative stress in NCDs patients through determination of Vit. D3, malondialdehyde (MDA) - a biomarker of oxidative stress, lipid profile test and thyroid hormone levels in fasting samples from 120 people (controls and patients). The different groups showed highly significant differences in Vit.D3, and between the MDA levels. Also, significant differences were found in the in the level of Vit. D3, MDA and triglyceride (TG) within the groups in comparison to control subjects. However, no significant differences were found between control subjects and patients in the levels TSH, T3, T4, cholesterol, LDL, and HDL. Gender of patients also contributed to the variation and highly significant differences were observed between the female and male in the level of Vit.D3 (P<0.0001) and female subjects were found to be deficient of Vit.D3 when compared with control (20.71±1.471) and (34.54±1.336) respectively. On other hand, gender had no effect on the variation in MDA levels and no significant differences were present between the female and male subjects. The present study, suggests that, Vit.D3 deficiency may not play a very important role in the increased oxidative stress status as seen in NCDs patients.